Tax aggressiveness, corporate sociai responsibility, and capital lntensity: Comparasion before and during the Covid-19 pandemic (Asian Journal of Economics and Business Management, 2022)
This research discusses tax aggressiveness, corporate social responsibility, and capital intensity before and during the COVID-19 pandemic. COVID-19 is still a popular topic today. The COVID-19 has not only affected the health sector but also the economies of almost all parts of the world. The phenomenon of COVID-19 raises discussions about whether there have been changes in company actions before and during the pandemic. Many companies have been negatively affected by the pandemic, but there are some businesses that have survived and remain stable. The findings of this study can be used as a monitoring method to inform stakeholders about company performance both before and during the pandemic. The time frame used in the study was 2018 to 2021. The population in this study was taken from the food and beverage industry listed on the Indonesia Stock Exchange (IDX). The data used was obtained from the company's annual report. The results of this study show that there were differences in tax aggressiveness, disclosure of corporate social responsibility, and capital intensity before and during the pandemic. There was an increase in tax aggressiveness during the COVID-19 pandemic due to the provision of tax incentives by the government, which was seen by companies as a loophole to practice tax aggressiveness. CSR also increased during the pandemic because it is used as a risk management strategy and to increase profits. Meanwhile, the decrease in capital intensity was due to a decrease in the company's fixed assets during the pandemic. Companies are trying to maximize the use of fixed assets and reduce costs that can reduce company profits. Further research is expected to use other variables and conduct research in different sectors with a larger number of samples.